PEMANFAATAN PANGAN LOKAL UNTUK PRODUKSI TORTILLA FUNGSIONAL BERBASIS LABU KUNING - If'all If'all; Mappiratu Mappiratu; Syahraeni Kadir (Jurnal Pengolahan Pangan, 2018)
Pumpkin is a source of nutrition potential to be developed as an alternative food substance by processing it to form processed food such as snack in addition to serving it as steamed, boiled, fried, and baked food or cooking it with other substances. Pumpkin contains 78.77% carbohydrate, 3.74% protein, 1.34% fat, and 2.80% raw fiber. The research aimed at studying the chemical and organoleptic qualities of pumpkin based tortilla produced from the best ratio of pumpkin, cassava and sweet potato. The research used a Completely Randomized design with a single factor of various weights of pumpkin addition. The treatment tested were seven levels of pumpkin weights including 500 g, 750 g, 1000 g, 1250 g, 1500 g, 1750 g and 2000 g. Each treatment was replicated thrice; therefore, there were 21 experimental units. Parameter tested were chemical characteristics of the tortilla such as carotene content, water content and ash content, and organoleptic quality including color, aroma, taste, crisp and performance of the tortilla. The research results showed that the pumpkin significantly affected all chemical characteristics and all organoleptic qualities except aroma quality. The contents of carotene, water and ash increased with raising pumpkin weights. The level of panelists’ predilection on tortilla decreased with increasing use of pumpkin. The ratio of 1000 g of pumpkin to 1000 g cassava and 250 g sweet potato fluor was the best formula for producing the best tortilla chemical and organoleptic qualities.